Soil-based biochar and foliar-spraying of chitosan enhances the phytochemical traits of yarrow (Achillea millefolium L.) under varying moisture levels - Farnaz Rezaei-Adl; Abdolah Ghasemi Pirbalouti; Touraj Rahimi; Faezeh Rajabzadeh; Hamid Mozafari (Scientific Reports)
Abstract Yarrow (Achillea millefolium L.) is an important medicinal and aromatic plant the active biologically compounds in particular essential oil is used as raw material in the pharmaceutical, food, and cosmetics industries. The impacts of the foliar spraying of chitosan (control and 2.5 g/L chitosan), the use of soil-based biochar (control and soil application at 2.0 kg/m2) under three moisture levels (irrigation at 80–85%, 60–65%, and 40–45% F.C.) on the agronomic traits and essential oil of yarrow were investigated. Results indicated that the deficit irrigation meaningfully decreased the yields of biological and flower, and essential oil yield, however, the contents of proline and essential oil under reduced irrigation significantly increased. According to essential oils analysis by GC-FID and GC/MS, the major constituents were α-pinene, 1,8-cineole, borneol, β-bisabolene, and caryophyllene oxide. A considerable increase and decrease were observed respectively in the monoterpenes and sesquiterpenes contents under reduced irrigation. The utilization of biochar along chitosan maintained higher secondary metabolites in particular α–pinene, β-myrcene, borneol, and 1,8-cineole under deficit irrigation. Generally, it appears that using the foliar spraying of chitosan along the soil application of biochar can be effective in improving the qualitative and quantitative features of the essential oil of A. millefolium in arid and semiarid climates.